(untitled) (African Multidisciplinary Journal of Research, 2022)
Most organization’s aim is to realize and uphold great performance. In order to achieve superior performance, organizations have enhanced strategy implementation process and concentrated efforts on strategy implementation imperatives. County governments in Kenya have fallen below expected performance due to challenges like high personnel emoluments, under-performance in own source revenue collection, low absorption of development allocation, high levels of pending bills, and weak budgetary controls. Management commitment is a strategy implementation imperative that could help in resolving these challenges and therefore this study sought to establish the effect of management commitment in addressing the county government performance. Descriptive and explanatory research design were adopted. Structured electronic questionnaire was sent to 252 respondents in the five counties in central region of Kenya. Descriptive and inferential statistics were used for analysis and overall model tested at 95 % confidence level. Results showed that management commitment has positive significant effect on the county government performance in the central region with a beta coefficient of 0.228 and p value of 0.000. Management commitment had an aggregate mean of 3.92 with a standard deviation of 0.740. Strategic Objectives had the highest mean of 4.12 the results indicated that top level personnel in the County have established quality policies and objectives with a mean of 4.16. Strategic direction and direct communication had almost the same means: 3.85 and 3.84 respectively. The summary shows that top level personnel in the Counties gave energy and loyalty to guiding implementation process towards attaining the County’s vision with a mean of 3.9. This study contributes to knowledge by providing a conceptual framework for the relationship between management commitment and county government performance, it makes contribution to policy by showing areas to emphasize on for improved performance of the county governments and also, on areas management should enhance in their plans and daily activities that will translate to better performance. Keywords: Strategy Implementation, County Government Performance, Management Commitment